Mild analgesics and the accident and emergency department--cost and safety more important than potency?. Issue 4 (December 1984) - Yates, D W; Laing, G S; Peters, K; Kumar, K
Abstract : A prospective controlled trial involving over 1000 patients did not reveal any difference between four drugs commonly used in accident and emergency departments for the relief of mild to moderate pain. There were no significant variations in therapeutic effect, side-effects or patient compliance. When considering the supply of analgesics which may be no more potent than those available without prescription from retail chemists, cost and safety are more important than analgesic effect. By restricting the choice of analgesics available, the accident and emergency department should be able to increase awareness among its staff of the actions and side-effects of a small number of prescribed drugs and to contain costs.